Crimson peak : the official movie novelization - Holder, Nancy; Toro, Guillermo del, 1964-; Robbins, Matthew (London : Titan Books, 2015)
In the aftermath of a family tragedy, an aspiring author is torn between love for her childhood friend and the temptation of a mysterious outsider. Trying to escape the ghosts of her past, she is swept away to a house that breathes, bleeds...and remembers.
Keywords: Horror tales; Film novelizations